Effectiveness of Task-Based Language Teaching in Enhancing Junior High School Students’ Simple Sentence Construction - Anggreini, Fany; Pratiwy, Devi (JOURNAL OF LANGUAGE, 2026)
This research investigates the effectiveness of Task-Based Language Teaching (TBLT) in improving simple sentence construction among second-year students at MTS Asmah Zaijuli Hamid, Hamparan Perak. Using a quantitative pre-experimental design with one group pretest-posttest, 20 eighth-grade students were selected through purposive sampling. Data were collected through written tests measuring five aspects of simple sentences: main clause, subject, predicate, verb, and vocabulary. The treatment followed Willis's three-stage TBLT procedure: pre-task, task-cycle, and language focus. The findings indicate that TBLT significantly enhances learners' grammatical performance, particularly in constructing simple sentences. This improvement can be attributed to the interactive and meaning-focused nature of TBLT, which facilitates both linguistic accuracy and communicative competence. The mean score improved from 64 (good category) in the pretest to 81 (very good category) in the post-test. Hypothesis testing using paired sample t-test revealed t-count (2.98769) > t-table (2.10092) at α = 0.05, indicating a significant effect of TBLT. These findings demonstrate that TBLT significantly enhances students' ability to construct simple sentences. The approach proves effective because it provides authentic contexts for language use, encourages student interaction, and offers systematic scaffolding. This research contributes empirical evidence of TBLT's effectiveness in teaching grammar at the Indonesian junior high school level. Recommendations are provided for teachers, students, and future researchers.